Language and Communicative Functions as well as Verbal Fluency in Children with High-Functioning Autism - Borkowska, Aneta Rita (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
The study was designed to investigate selected aspects of language and communicative functions as well as verbal fluency in children with HFA. The study group comprised 51 children, aged 10-12, including 23 subjects diagnosed with High-Functioning Autism, with normal IQ and able to communicate verbally, as well as a group of 28 controls. The applied tools included RHLB-PL Battery, a verbal fluency task and WISC-R Vocabulary subtest. The findings show significantly varied profiles of the investigated functions in the group of children with HFA. In comparison with their peers, they have greater difficulties drawing logical conclusions from stories. They find it difficult to grasp humour conveyed by linguistic expression and by metaphors, presented with the use of both linguistic materials and drawings. They have lower capacitates for understanding prosodic (emotional and language) aspects of utterances addressed to them. It has been established that they are able to correctly understand isolated words and recognize their designates despite the present distractors. No generalized deficits have been found in the subjects’ verbal fluency. In comparison to the controls, the children with HFA generated similar number of words matching the phonemic criterion. Furthermore, their performance showed no perseverations, and comparably frequent clustering and switching. Lexicon matching the semantic criterion was more difficult to access for the children with HFA than for the controls. Children with HFA had difficulties in defining familiar words.